Odpowiedzi

2010-03-02T17:44:41+01:00
A)(4-x)^2 - (x+1)^2>5
16-8x+x² -x²-2x-2 > 5
-8x-2x > 5+2-16
-10x > -9 / : (-10)
x < ⁹/₁₀
rozwiązaniem jest zbiór (-∞ ; ⁹/₁₀)

b)(x+1)^2 -(x-1)^2+(x-1)*(x+1)<(1-x)^2
x²+2x+2-x²+2x-2+x²-1 < 1-2x+x²
2x+2x+2x < 1+1-2+2
6x < 2 / : 6
x < ²/₆
x < ¹/₃
rozwiązaniem jest zbiór (-∞ ; ¹/₃)

c)3/4x -0,75(x-1)^2 +3/4x^2<0
¾ x - ¾ (x²-2x+1)+ ¾ x² < 0
¾ x - ¾x² +³/₂x- ¾ + ¾ x² < 0
¾ x+³/₂x < ¾
¾ x + ⁶/₄ x < ¾
⁹/₄x < ¾ / * ⁴/₉
x < ⅓
rozwiązaniem jest zbiór (-∞ ; ¹/₃)

d)(3+x)^2 ≥ x^2-3
9+6x+x² ≥ x²-3
6x ≥ -3-9
6x ≥ -12 / : 6
x ≥ -2
rozwiązaniem jest zbiór <-2 ; +∞ )

e)(2x+1)^2<4(x+3)^2+5
4x²+4x+1 < 4 (x²+6x+9) +5
4x²+4x+1 < 4x²+24x+36+5
4x-24x < 36+5-1
-20x < 40 / : (-20)
x > -2
rozwiązaniem jest zbiór (-2 ; +∞ )

f)(4x-1)^2≥ 4(3-2x)^2+5
16x²-8x+1 ≥ 4(9-12x+4x² ) +5
16x²-8x+1 ≥ 36 - 48x +16x² +5
-8x+48x ≥ 36+5-1
40x ≥ 40 / : 40
x ≥ 1
rozwiązaniem jest zbiór <1 ; +∞ )